An introduction to sports law in Malaysia : legal guidelines for sportspersons and sports administrators - Hassim, Zaidi (LexisNexis (Malayan Law Journal), 2005)
An Introduction to Sports Law in Malaysia: Legal Guidelines for Sportspersons and Sports Administrators is the first ever published book exclusively highlighting the legal aspects of Sports in Malaysia. This book discusses the many complex legal issues confronting Malaysian sports today. It is designed to create a new level of awareness of the extent of which those ties between Sports and the law exist.